2002
DOI: 10.1002/1521-4141(200206)32:6<1584::aid-immu1584>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Ly-6A is critical for the function of double negative regulatory T cells

Abstract: We have recently demonstrated that CD3+CD4–CD8– double negative (DN) T cells can down‐regulate allogeneic immune responses both in vitro and in vivo by killing activated syngeneic CD8+ T cells. The goal of this study was to identify molecules that are crucial for DN T cell‐mediated suppression. We demonstrate that Ly‐6A (Sca‐1) is highly expressed on DN T cells. Incubation with IL‐10 significantly reduced Ly‐6A expression and the function of DN T cells. DN T cell‐mediated killing was significantly reduced when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 46 publications
3
30
0
Order By: Relevance
“…We have recently demonstrated in three different mouse models that DN T cells have a regulatory function and can suppress immune responses mediated by CD8 ϩ or CD4 ϩ T cells that are syngeneic to the DN T cells (7,8,13,14,29,30). Next, we studied whether DN T cells from reconstituted recipient mice were able to suppress proliferation of syngeneic antihost CD8 ϩ T cells.…”
Section: Dn T Cells Are Able To Suppress Antihost Cd8 ϩ T Cellssupporting
confidence: 90%
See 1 more Smart Citation
“…We have recently demonstrated in three different mouse models that DN T cells have a regulatory function and can suppress immune responses mediated by CD8 ϩ or CD4 ϩ T cells that are syngeneic to the DN T cells (7,8,13,14,29,30). Next, we studied whether DN T cells from reconstituted recipient mice were able to suppress proliferation of syngeneic antihost CD8 ϩ T cells.…”
Section: Dn T Cells Are Able To Suppress Antihost Cd8 ϩ T Cellssupporting
confidence: 90%
“…We and others have demonstrated that the infusion of single MHC class I locus-mismatched donor lymphocytes may lead to permanent acceptance of donor-specific skin and heart allografts without the need for nonspecific immunosuppression in H-2K bm1 (7,8)-, H-2K b (9, 10)-, and H-2L d (11)(12)(13)(14)-mismatched mouse models. Likewise, it has been shown that the infusion of recipient cells that have been genetically engineered to express a donor MHC class I molecule can also induce transplantation tolerance (10,15,16).…”
mentioning
confidence: 99%
“…We have demonstrated that mouse DN-Treg specifically can eliminate activated syngeneic anti-donor CD4 + T cells, CD8 + T cells, and B cells [22,23,25,26]. Furthermore, adoptive transfer of DN-Treg leads to significant prolongation of donor-specific skin and heart allografts in a single MHC-mismatched murine model [22,23,27].…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, we found that TCRab + CD3 + CD4 -CD8 -(double-negative, DN) T cells possess immuneregulatory functions and play an important role in the development of tolerance post-transplantation [22][23][24][25]. We have demonstrated that mouse DN-Treg specifically can eliminate activated syngeneic anti-donor CD4 + T cells, CD8 + T cells, and B cells [22,23,25,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation